Preliminary study on thermal–hydraulic behavior of loss-of-flow accident in deep pool-type nuclear reactor. (1st June 2022) - Wang, Gongqing; Yue, Zhiting; Sun, Rulei; Li, Dongyang; Liu, Xingmin; Wang, Bo; Tian, Ruifeng
Highlights: The transient thermal–hydraulic behavior of LOFA in DPNR is analyzed. The effects of flap valve opening criteria on LOFA are revealed. The effects of FRC in connection pipe on LOFA are revealed. The core flow oscillation caused by inertia tank is alleviated by opening flap valve. Abstract: Deep pool nuclear reactor (DPNR) is a novel pool-type reactor, which has shown great potential in seawater desalination and district heating. In this paper, the thermal–hydraulic behavior of loss-of-flow accident (LOFA) in DPNR were investigated by RELAP5. The parametric analyses were also carried out to reveal the effects of flow resistance coefficient (FRC) in connection pipe and flap valve opening criteria on thermal–hydraulic behavior of LOFA in DPNR. The results showed that the LOFA process could be divided into coast-down phase, oscillation phase and natural circulation phase, and two peaks of clad peak temperature appeared. Besides, the parametric analysis showed that increasing FRC in connection pipe and failure of flap valve can make the first and second peak of clad peak temperature larger, respectively. The decrease of flap valve opening criteria made flap valve open earlier, and inertia tank performance was weakened when flap valve opened in coast-down phase.